A QoS multicast routing protocol for dynamic group topology - Layuan, Li; Chunlin, Li (Information sciences, 2005)
Multicast routing is establishing a tree which is rooted from the source node and contains all the multicast destinations. A multicast routing tree with multiple QoS constraints may be the tree in which the delay, delay-jitter, packet-loss and bandwidth should satisfy the pre-specified bounds. This paper discusses the multicast routing problem with multiple QoS constraints, which may deal with the delay, delay-jitter, bandwidth and packet-loss metrics, and describes a network model for researching the routing problem. It presents a QoS multicast routing protocol with dynamic group topology (QMRPD). The QMRPD attempts to significantly reduce the overhead of constructing a multicast tree with multiple QoS constraints. In MPRMQ, a multicast group member can join or leave a multicast session dynamically, which should not disrupt the multicast tree. It also attempts to minimize overall cost of the tree, and satisfy the multiple QoS constraints and least cost's (or lower cost) requirements. In this paper, the proof of correctness and complexity analysis of the QMRPD are also given. Simulation results show that QMRPD is an available approach to multicast routing decision with dynamic group topology.